Conflicts in the knowledge society : the contentious politics of intellectual property - Haunss, Sebastian (Cambridge, UK : Cambridge University Press, 2013)
'In Conflicts in the Knowledge Society, Sebastian Haunss demonstrates how conflicts relating to the international system of intellectual property have resulted in new cleavages in the knowledge society. Furthermore, he argues that new collective actors have emerged from these conflicts with the ability to contest the existing dominant order. With a focus on political opportunity structures, collective action networks and framing strategies, he combines a theoretical discussion of social change in the knowledge society with empirical analyses of four recent developments: software patents in Europe, access to medicines, Creative Commons licensing and Pirate Parties'--
Introduction -- The politicization of intellectual property -- Conflict and change in the knowledge society -- Software patents in Europe -- Access to medicines -- Pirates and commoners -- Conclusion : new cleavages and new collective actors.
Includes bibliographical references (pages 237-265) and index.
Keywords: Intellectual property -- Political aspects